The Quest for Third Gender Equality: Challenges and Implications for Islamic Law and Muslim Women's Sustainability in Malaysia - Ramli, Mohd Anuar; Kasa, Annuar Ramadhon; Muhamad Sharifuddin, Nurhidayah; Yusof, Muhammad Yusri; Hassan, Paiz (Universitas Islam Negeri Jakarta, 2024)
Fundamentally, men and women constitute the two primary gender binaries in the construction of human society. Khunthā, however, refers to individuals with anomalies. There are no specific exemptions regarding this group in the discourse of Islamic law. Recently, the third gender group has been advocating for equal rights with the binary gender group. Although the third gender is not recognized in Islam, efforts to acknowledge them have been increasing in certain Islamic nations, including Malaysia. They argue that they are assigned to an incorrect gender. Consequently, individuals transition to a different gender identity, such as trans-women or trans-men. The universalism of Western human rights serves as inspiration for the demand for third-gender rights, which opposes local religious and cultural norms. Additionally, this paper explores the implications of third-gender recognition on Muslim women and the sustainability of Islamic law in Malaysia. This qualitative study employs the library research process to collect relevant documentation to achieve the objective. Content analysis of the gathered material was conducted inductively to assess the implications of the third gender claim on Islamic law and women. According to the study's findings, recognizing the third gender's ambition for equality would lead to modifications in laws and the diminishment of women's rights as they would have to share resources and benefits with biological males. AbstrakSecara fundamental, laki-laki dan perempuan membentuk dua biner gender utama dalam konstruksi masyarakat manusia. Khunthā, bagaimanapun, merujuk pada individu dengan anomali. Dalam diskursus hukum Islam, tidak ada pengecualian khusus mengenai kelompok ini. Baru-baru ini, kelompok gender ketiga telah mulai memperjuangkan kesetaraan hak dengan kelompok gender biner. Meskipun gender ketiga tidak diakui dalam Islam, upaya untuk mengakui mereka semakin meningkat di beberapa negara Islam termasuk Malaysia. Mereka berargumen bahwa mereka ditetapkan pada gender yang tidak sesuai. Akibatnya, individu bertransisi ke identitas gender yang berbeda, seperti trans-wanita atau trans-pria. Universalitas hak asasi manusia Barat menjadi inspirasi bagi tuntutan hak kelompok gender ketiga ini, yang bertentangan dengan norma-norma agama dan budaya lokal. Artikel ini mengeksplorasi implikasi pengakuan gender ketiga terhadap perempuan Muslim dan keberlanjutan hukum Islam di Malaysia. Penelitian kualitatif ini menggunakan proses penelitian kepustakaan secara menyeluruh untuk mengumpulkan dokumentasi yang relevan guna mencapai tujuan tersebut. Analisis konten terhadap bahan yang dikumpulkan dilakukan secara induktif untuk menilai implikasi tuntutan gender ketiga terhadap hukum Islam dan perempuan. Berdasarkan temuan penelitian, pengakuan terhadap ambisi kesetaraan gender ketiga akan menyebabkan modifikasi dalam hukum dan pengurangan hak-hak perempuan karena mereka harus berbagi sumber daya dan manfaat dengan laki-laki biologis.